Role of Transcutaneous Perianal Ultrasonography in Evaluation of Perianal Fistulae with MRI Correlation - Singh, Amandeep; Kaur, Gurpreet; Singh, Jai Inder; Singh, Gauravdeep (Indian Journal of Radiology and Imaging, 2022)
Purpose: The aim of this study was to evaluate the role of transcutaneous perianal ultrasonography (TPUS) in patients with perianal fistula and to correlate the findings with magnetic resonance imaging (MRI) as gold standard.Materials and Methods: This prospective study included patients who presented with suspicion of perianal fistula. After clinical examination, TPUS and MRI of perianal region were performed on each of them. Clockwise position of internal opening of the fistula was described. The entire length of the tract was evaluated up to the external opening. Also, any ramifications along the primary tract were described. Parks et al and St James's University Hospital MR Imaging Classification of Perianal Fistulas were used for classifying the fistulas.Results: Out of total 37 patients, the most common age group of presenting individuals was 45 to 60 years with male to female ratio of 6.4:1. There was excellent agreement between TPUS and MRI for detecting primary fistulous tract with kappa correlation coefficient of 1. The kappa correlation coefficient for detecting secondary fistulous tracts and abscess on TPUS and MRI was 0.839 and 0.937 showing excellent agreement. Moderate agreement was seen with kappa correlation coefficient of 0.839 in the detection of internal opening on TPUS and MRI.Conclusion: TPUS showed promising results in diagnosis and classification of perianal fistulae with MRI as gold standard. A wide availability, cost-effectiveness, and better tolerability of TPUS can make it an imaging modality of first choice for evaluating perianal fistulae.
Keywords: MRI; perianal abscess; perianal fistula; TPUS; transcutaneous perianal ultrasonography